2021
DOI: 10.2147/cmar.s291029
|View full text |Cite
|
Sign up to set email alerts
|

Giant Fungated Locally Advanced Breast Carcinoma Responded to Hypofractionated Radiotherapy Combined with Apatinib: A Case Report and Literature Review

Abstract: Locally advanced breast cancer (LABC) is frequently encountered in clinical practice. Primary systemic therapy is regarded as the cornerstone of LABC management to downstage the disease and enable surgery. However, multiple lines of systemic agents may fail to control tumor growth in a considerable number of patients, and few options remain available for such patients. Here, we present a case of triple-negative, right breast cancer that progressed aggressively despite 3 lines of standard chemotherapy. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The dressing on the wound was changed frequently and this seriously affected the quality of life of the patient. After conducting a literature review, we found that a similar phenomenon occurred in some other cases [7,18–20]. We suggest that this may be related to the mechanism of action of Apatinib, as it induced apoptosis and inhibits cell proliferation by blocking the VEGF pathway.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…The dressing on the wound was changed frequently and this seriously affected the quality of life of the patient. After conducting a literature review, we found that a similar phenomenon occurred in some other cases [7,18–20]. We suggest that this may be related to the mechanism of action of Apatinib, as it induced apoptosis and inhibits cell proliferation by blocking the VEGF pathway.…”
Section: Introductionsupporting
confidence: 62%
“…But due to the significant anticancer of Apatinib, a large cavity formed rapidly in the primary tumor after the size of the tumor reduced, and this is not the first report of such an occurrence. A few case reports have also mentioned a similar phenomenon [7,[18][19][20], and we summarize have these cases in Table 1. Surgery or RT is generally palliative when cavities and necrosis occur.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Importantly, apatinib can normalize the surviving tumor vessels, improve the delivery of chemotherapy drugs through reducing the pressure between tumor tissues, and enhance the efficacy of chemotherapy 32 . Recently, the efficacy of apatinib in advanced TNBC with failure of chemoradiotherapy has been confirmed in several studies [33][34][35] . In a retrospective study, combination of apatinib and capecitabine achieved a better PFS and tolerable toxicity compare with capecitabine monotherapy, which may regard as one of the options of the third-line treatment for advanced TNBC 36 .…”
Section: Yesmentioning
confidence: 99%
“…In recent years, apatinib combined with radiotherapy has shown good survival benefits in the treatment of non-small cell lung cancer, breast cancer, liver cancer, and cervical cancer ( Zhang et al, 2018 ; Liu et al, 2021 ; Ma et al, 2021 ). At present, there have been as many as 25 clinical studies of apatinib combined with radiotherapy, and that number seems to be increasing ( http://clinicaltrials.gov/ ).…”
Section: Introductionmentioning
confidence: 99%